Profit Margin provided by application of a fertilizer NPK at different levels in coffee plants irrigated - Oliveira, Diego Humberto de; Guimarães, Rubens José; Junior, Luiz Gonzaga de Castro; Silva, Douglas Ramos Guelfi; Villela, Gabriel Mendes; Andrade, Fabrício Teixeira (Coffee Science - ISSN 1984-3909, 2017)
The lack of management preparation inherited down from past regulations interferes in economic results of production. During the productive cycles the quantity of fertilizers are effected without the technical recommendations, which may economically render the production. The product, therefore, demands information to act strategically on its own business. The main objective for this project was analyzed the profit margin provided by application of a fertilizer NPK at different levels in coffee plants irrigated. The analyses contemplated the harvests of 2012/2013 and 2013/2014 of an experiment carried out at the Federal University of Lavras (UFLA). The outlining was made in random blocks with six treatments and four repetitions, being six levels of fertilization with fertilizers containing N, P2O5 e K2O that were from 10, 40 ,70 ,100 ,130 and 160% of recommended standards for coffee producers of dry farming. There was a significant effect from the levels of fertilizers in effect in relation with the productivity on the biennium, and the maximum production was reached with the application of the fertilizer on the level of 145,57% of the recommended standard. The optimal economic production occurred with the application on the level of 118,12%. The economic maximum and optimal productions on the biennium generated a gross margin of R 18.205,73/ha and R 19.127,81/ha respectively, considering only the costs of fertilizers that was the variable factor.